2003
DOI: 10.1095/biolreprod.102.006197
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Loss of Oct-4 and Pluripotency in Cultured Rodent Blastocysts and Derivative Cell Lines1

Abstract: The POU transcription factor Oct-4 is essential for the pluripotent character of the mouse inner cell mass (ICM) and derivative embryonic stem (ES) cells. We analyzed the expression of Oct-4 during culture and establishment of cell lines from mouse and rat preimplantation embryos. Oct-4 was rapidly lost in primary outgrowths of the majority of cultured embryos prior to any evidence of morphological differentiation. Oct-4 persisted in only a minority of strain 129 cultures, which can go on to give ES cells. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
101
1
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(109 citation statements)
references
References 35 publications
5
101
1
1
Order By: Relevance
“…MRPC were isolated from adult rat kidneys using culture conditions that were similar to those used for the culture of bone marrow-derived multipotent adult progenitor cells with the exception that we did not deplete the cells that were positive for CD45 or glycophorin A (27). The source for the rat kidneys were 2-to 4-mo-old Fisher rats, including Oct4 ␤-Geo transgenic rats that contain a transgene that combines a neomycinresistance gene with a lacZ reporter under the control of 3.6 kb of the mouse Oct4 upstream sequence, including both proximal and distal enhancers (gift from Dr. Austin Smith, University of Edinburgh, Edinburgh, Scotland) (28). Oct4 is a POU family transcription factor that is expressed in embryonic and adult stem cells and immortalized nontumorigenic cell lines and tumor cells but not in differentiated cells (27,29 -31).…”
Section: Isolation Of Mrpcmentioning
confidence: 99%
“…MRPC were isolated from adult rat kidneys using culture conditions that were similar to those used for the culture of bone marrow-derived multipotent adult progenitor cells with the exception that we did not deplete the cells that were positive for CD45 or glycophorin A (27). The source for the rat kidneys were 2-to 4-mo-old Fisher rats, including Oct4 ␤-Geo transgenic rats that contain a transgene that combines a neomycinresistance gene with a lacZ reporter under the control of 3.6 kb of the mouse Oct4 upstream sequence, including both proximal and distal enhancers (gift from Dr. Austin Smith, University of Edinburgh, Edinburgh, Scotland) (28). Oct4 is a POU family transcription factor that is expressed in embryonic and adult stem cells and immortalized nontumorigenic cell lines and tumor cells but not in differentiated cells (27,29 -31).…”
Section: Isolation Of Mrpcmentioning
confidence: 99%
“…These results supported the earlier report, in which Ouhibi et al (1995) indicated that rat ICM cells differentiated rapidly after 3-6 days in primary culture even when they were cultured on fibroblast feeder layers. Potential of cultured ICM cells decrease rapidly due to the loss of POU-domain transcription factor Oct-4 expression following culture in vitro, because expression of Oct-4 is essential for cells to maintain their pluripotency (Buehr et al, 2003). Rat chimera had not been gengerated in this study, it might be the same reason, but it still needs to be investigated.…”
Section: Discussionmentioning
confidence: 93%
“…So far, there have only been reports demonstrating the production of rat chimeras by aggregation of 8-cell embryos or morulae (Weinberg et al, 1985;Clegg et al, 1991), or by 8-cell embryos injected with ICMs (Buehr et al, 2003). Here we have generated rat chimeras by SD or DA ICM exchange injection between SD and DA rat strains.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations